Longitudinal analysis of the enteric virome in paediatric subjects from the Free State Province, South Africa, reveals early gut colonisation and temporal dynamics - Mogotsi, Milton Tshidiso; Ogunbayo, Ayodeji Emmanuel; Bester, Phillip Armand; O'Neill, Hester Gertruida; Nyaga, Martin Munene (Virus research, 2024)
•Gut microbial colonisation in infants is a crucial, yet intricate, process, characterised by minimal diversity at birth that increases with age.•The infant gut virome is dominated by eukaryotic viruses, consisting primarily of human enteric viruses and non-human dietary viruses.•The infants’ gut haboured high abundance of gastroenteritis-associated viruses, despite the absence of clinical symptoms.•The presence of plant viruses in the gut of infants who are not exposed to solid food could suggest vertical transmission from mother to infant, or possibly, contact between infant and other family members. The gut of healthy neonates is devoid of viruses at birth, but rapidly becomes colonised by normal viral commensals that aid in important physiological functions like metabolism but can, in some instances, result in gastrointestinal illnesses. However, little is known about how this colonisation begins, its variability and factors shaping the gut virome composition. Thus, understanding the development, assembly, and progression of enteric viral communities over time is key. To explore early-life virome development, metagenomic sequencing was employed in faecal samples collected longitudinally from a cohort of 17 infants during their first six months of life. The gut virome analysis revealed a diverse and dynamic viral community, formed by a richness of different viruses infecting humans, non-human mammals, bacteria, and plants. Eukaryotic viruses were detected as early as one week of life, increasing in abundance and diversity over time. Most of the viruses detected are commonly associated with gastroenteritis and include members of the Caliciviridae, Picornaviridae, Astroviridae, Adenoviridae, and Sedoreoviridae families. The most common co-occurrences involved asymptomatic norovirus-parechovirus, norovirus-sapovirus, sapovirus-parechovirus, observed in at least 40 % of the samples. Majority of the plant-derived viruses detected in the infants’ gut were from the Virgaviridae family. This study demonstrates the first longitudinal characterisation of the gastrointestinal virome in infants, from birth up to 6 months of age, in sub-Saharan Africa. Overall, the findings from this study delineate the composition and variability of the healthy infants’ gut virome over time, which is a significant step towards understanding the dynamics and biogeography of viral communities in the infant gut.